Internalisation of Islamic value on ethics in corporate culture in Malaysia - Salleh, Kamaliah; Hamid, Noor ‘Ashikin; Harun, Noraida; Bidin, Asiah; Abd Ghadas, Zuhairah Ariff; Salleh, Ahmad Zahid (Universiti Teknologi MARA, Kelantan, 2018)
Islam sets a complete guidance and ground rule in order to regulate the living of one’s life. It is within this rule that Islam introduces the detailed concept of social and ethical behaviour for us to live with. It applies not only to persons as individuals but also adopted in business practice by organizations and corporate entities. Ethics are deemed to be crucial element of managerial competence and governance in corporate code nowadays. The Malaysian Code of Corporate Governance has since been developed through years and gone through numbers of review in order to enhance business ethics and practice. The current edition which has been published in April 2017 takes on a new approach to promote greater internalisation of ethics into the corporate governance culture. This study aims primarily to explore the extent of Islamic value on ethics contributing to the current Code of Corporate Governance (‘MCCG 2017’) towards reinforcing the corporate culture in Malaysia. The study is based on qualitative approach which employs library research method for data collection. The study analyses various texts such as books, journals, reports and code. The study reveals that there are numbers of authentic Islamic approach to ethics which are in line with the current corporate code with regard to ethics and governance which are currently applicable in Malaysia.